Lifestyle habits and impact of the Mediterranean diet on facial acne severity in French women: a case-control study. Issue 2 (13th May 2022) - Ah-Thiane, Laurie; Nguyen, Jean Michel; Khammari, Amir; Dréno, Brigitte
Abstract : Acne is a common benign inflammatory disease, but it has a significant psychosocial impact. The role of the diet in the development of acne is controversial. Some daily foods such as milk and fast-release sugars tend to promote acne. The Mediterranean Diet (MD) is based on virgin olive oil and nuts that are rich in polyphenols with anti-inflammatory properties. The aim of this study was to assess an association between the adherence to the MD and the severity of facial acne in French women. A case-control observational study was conducted in Nantes Hospital (France). Based on a validated PREvención con DIeta MEDiterránean questionnaire, the adherence to the MD was assessed. The Global Evaluation Acne severity score was assessed by a trained dermatologist. Forty women with mild-to-severe acne and 40 control subjects were included. A global linear model identified a significant negative correlation between the severity of acne and the adherence to the MD in acne patients (regression coefficient = −0.17; P = 0.017). This was the first study conducted in France to investigate the relationship between the adherence to the MD and the severity of facial acne in women. This study confirmed the importance of using a holistic approach for acne management. Further studies are needed to confirm our findings.